Keselarasan Penggunaan Big Data dengan Perlindungan Data Pribadi - moh hamzah hisbulloh (Jurnal Ilmiah Dinamika Hukum, 2022)
Abstrack: The rapid development of technology affects various aspects of life, one of the effects of technological developments is felt in the process of data management systems which are almost entirely digital-based, this affects the availability of data recorded in digital form which is very abundant, resulting in the creation of a digital system known as Big Data. On the other hand, the rapid development of technology creates new problems, problems that often arise in the current era regarding the protection of personal data. Regulations related to the protection of personal data, both in government and private institutions, have been regulated in several laws and regulations, but in their implementation the rules governing personal data protection are not sufficient to provide protection for personal data collected in Big Data, both in government institutions and private. Therefore, this study analyzes the alignment of the use of Big Data technology with public or consumer privacy regarding the protection of personal data. The research method uses a literature review with a conceptual-analytic approach. The data used are various journals related to the topic the author is studying, related laws and regulations and several news sources from print and electronic media. The use of big data must be balanced with strong protections related to personal data protection, in practice in Indonesia the lack of legal rules related to personal data protection has resulted in many cases of data leakage.